Expansão da silvicultura de eucalipto no bioma cerrado: uma análise sob a perspectiva dos fatores físicos e socioeconômicos - Lopes, Cassiomar Rodrigue (2013)
This work presents and discusses the results about the expansion of the cultivation of eucalyptus (Eucalyptus spp) in the Cerrado biome, including the analysis of related variables in this process. The motivation for this research came from the recognition, using data from the Brazilian Institute of Geography and Statistic, of the expansion of this crop, mainly in the state of Mato Grosso do Sul, where it was verified in the last three decades changes in the landscape with the replacement of cattle raising and agriculture. At the same time, there was a regression in eucalyptus plantations in Bahia’s west. It can be argued that this expansion and regression of areas are connected to the presence of forest-based industries in the region that needs this raw material. Therefore, this study sought to identify areas where they are being held eucalyptus plantations in the Cerrado with 2006 census data. These locations were chosen based on these information, and the mapping of the highlighted counties according to the data from the agricultural census. Then it was analyzed the variables physical, political economical and social policies in the producing regions. Based on these features were pointed the prone areas for the expansion of eucalyptus plantation in the Cerrado. In general, the results show that there are a predominance of some characteristics in the choice of areas to be cultivated, as a predominant deep sandly quartzly soils, relief in the class of 0 º to 8 º of declivity and proximity to highways and rivers around 5 km and 3 km, respectively. Another important result of this research, obtained by the intersection of the areas of eucalyptus to the Cerrado and the map of land use (PROBIO), indicates that the expansion of this crop is occurring over areas with remnant Cerrado vegetation.